Sosialisasi dan Edukasi Pencegahan Tindakan Perundungan di SDN 40 Hulontalangi Kota Gorontalo - Juniarti, Gita (LPPM Universitas Timor, 2024)
Bullying is one of the problems in the school. Bullying does not just happen to adults and teenagers. Even children at the elementary school level can potentially become bullying perpetrators. Therefore, its service aims to educate on bullying and prevent bullying-related behavior. The service activity was carried out at SDN 40 Hulontalangi. As first step, the community service team made observations regarding the understanding of students at the school regarding their understanding of bullying. The students did not know about bullying, but they often experienced acts related to verbal, relational, and physical bullying. The results of the observations have collaborated with interviews with teachers and principals at the school. The activities carried out were in the form of outreach about bullying and education about bullying prevention. The activity was delivered in the form of lectures, delivery via video, and games in the form of role-playing between students at SDN 40 Hulontalangi. The result of this empowerment is students' understanding of bullying increases. This activity concludes that students understand that bullying is a disgraceful act and must be avoided. They also understand what actions should be taken if they experience bullying and take action if their friends become victims of bullying.